Antibiotic Use and Outcomes in Young Children Hospitalized With Uncomplicated Community-Acquired Pneumonia. (9th March 2022) - Hofto, Meghan E; Samuy, Nichole; Pass, Robert F
Abstract: Background: We aimed to compare children aged 36 months or younger hospitalized with uncomplicated community-acquired pneumonia (CAP) who are not treated with antibiotics to those treated with antibiotics in terms of clinical features and outcome measures. Methods: Administrative data and medical record review were used to identify patients from 3 to 36 months of age hospitalized from 2011 to 2019 with uncomplicated CAP. Patients were considered treated if they received antibiotics for >2 inpatient days and/or at discharge, and not treated if they received ≤2 inpatient days and no antibiotics at discharge. Untreated patients were compared to treated patients based on demographic features, clinical and laboratory results, and outcomes of interest, including illness severity, length of stay, and 30-day hospital readmissions. Results: Three hundred twenty-two CAP cases were included; 266 (83%) received antibiotics for >48 hours and/or at discharge. Fifty-six patients received ≤2 inpatient days of antibiotics and no antibiotics at discharge; the majority received no inpatient antibiotics. There were no differences between the 2 groups in illness severity, length of stay, or hospital readmissions. The proportion of patients treated with antibiotics decreased from 88% (2011–2013) to 66% during the most recent years studied (2017–2019). Conclusions: There was no difference in outcome of uncomplicated CAP in previously healthy children <36 months of age between those treated and not treated with antibiotics. Additional tools are needed to facilitate identification of viral CAP in young children and decrease unnecessary antibiotic use. Abstract : Guidelines indicate that all children hospitalized with community-acquired pneumonia should be treated with antibiotics. Experience shows that a significant proportion of patients with uncomplicated pneumonia who are <3 years of age will do well without antibiotic treatment.